Deployment of telemedicine as another mitigation tool during the COVID-19 pandemic in India - Payal Das; Amit Sharma (Elsevier, 2021)
Healthcare systems in resource scarce countries continue to face unprecedented challenges due to the COVID-19 pandemic, including saturation of healthcare system capacities. Data suggest that medical staff deployed for COVID-19 containment are at higher risk of exposure and thus greater susceptibility to infection, further decreasing the available workforce. Telemedicine, as an additional healthcare delivery approach, can circumvent hospital visits of non-critical COVID-19 patients and thus reduce exposure of both providers and non-COVID-19 patients. Widespread implementation of telemedicine at this watershed moment for healthcare system in India will establish a new public health delivery alternative that can cater to the COVID-19 pandemic and beyond.